Tailored for Impact: Analysis of a Customized Online Learning System for TNB Chargemen Exam Preparation - Idris A.; Mohamad A.; Mohamad M.S.; Abu Kassim N.F.; Awaludin M.A.; Noor S.M. (Springer Science and Business Media Deutschland GmbH, 2025)
SuKSES (Staff Knowledge and Skills Enhancement System), developed by Universiti Tenaga Nasional (UNITEN), is an innovative online learning system tailored for TNB staff preparing for chargemen competency examination. It offers advantages such as enhanced understanding through mastery learning approach, interactive learning, flexibility, adaptability, cost-efficiency, and pandemic readiness. The study?s mixed-methods approach reveals a strong correlation between satisfaction with SuKSES features and system usage. Results show overwhelming positive feedback, emphasizing its flexibility, alignment with exam topics, and effectiveness. SuKSES fills a research gap, showcasing the potential of specialized online platforms for professional development and challenging previous findings. It stands as a promising tool for improving competency exam outcomes. ? The Author(s).